METABOLIC SYNDROME: GENDER INEQUALITIES, INTERDISCIPLINARY CARE AND DECISION MAKING IN PUBLIC HEALTH - Freitas Macedo, Sthélio; Thamalla Mendes dos Santos, Shayene; Paula Santos Resende, Ana; Izabel Pezarini Jiacon, Milene; Gomide Nolasco de Assis, Joice (Revista Gênero e Interdisciplinaridade, 2026)
Metabolic syndrome (MS) constitutes one of the greatest challenges in global public health, characterized by a set of interrelated changes that substantially increase the risk of cardiovascular diseases, type 2 diabetes and mortality. It occurs especially in women, the elderly and individuals with low education. Such findings highlight structural inequalities that require an intersectional and interdisciplinary approach when formulating care strategies. This integrative review aimed to synthesize recent scientific evidence on the epidemiology, pathophysiological mechanisms and care and decision-making strategies related to MS. The search was carried out in June 2025 in the Scopus, PubMed, CINAHL, LILACS, SciELO, Google Scholar and Web of Science databases, using DeCS and MeSH descriptors, with a time frame from 2015 to 2025. Of the 1,238 studies initially identified, 10 met the inclusion criteria. The results showed a global prevalence of MS between 20% and 30%, with rates of 38.4% in the Brazilian adult population, especially in women, the elderly and individuals with low education. Studies have highlighted central mechanisms such as insulin resistance, chronic low-grade inflammation and endothelial dysfunction, in addition to serious clinical consequences. The need for multidisciplinary care models, cultural adaptation of clinical protocols and integration of digital technologies and artificial intelligence to optimize clinical decision-making and treatment personalization was also identified. It is concluded that tackling MS requires integrated interventions, robust public policies and investments in technological innovation, in addition to strengthening multidisciplinary care and the development of population-based preventive strategies.